One- and two-dimensional NMR studies on the conformation of DNA containing the oligo(dA)oligo(dT) tract. - Katahira, M (1988)
The resonances of the imino protons and all of the non-exchangeable protons (except for H5'/H5'') of d(CGCAAAAAAGCG)d(CGCTTTTTTGCG) have been assigned by means of one- and two-dimensional NMR spectroscopies. Qualitative analyses showed that the overall structure is of the B-form, but local conformational deviations exist. The NOEs between the imino protons of thymines and H2 of adenines suggest that the A-T base pairs are propeller-twisted to almost the same degree as in crystals. A remarkable chemical shift of H1' was observed for the residue located just before the oligo(dA)oligo(dT) tract, suggesting the presence of conformational discontinuity at the junctions between the oligo(dA)oligo(dT) tract and the other portions. Analyses of cross peaks in NOESY spectra between H2 of adenines and H1' of the 3'-neighbouring residues on the complementary strand revealed that the minor groove of the oligo(dA)oligo(dT) tract is narrow and compressed gradually, from 5' to 3', along the tract.